Bank Guarantee Functions As Distributor Guarantee To Customers Issued By Pt. Indonesian People's Bank (Persero) Tbk. - Siti Nurul Azizah; Rosanini Daga; Samad, Abd (ASIAN PUBLISHER, 2023)
This research was conducted to find out the functions and procedures of the Bank Guarantee as a guarantor for distributors to customers issued by PT. Bank Rakyat Indonesia (Persero) Tbk. This type of research uses qualitative research with the type of field research (Field Research). Field research is a field research procedure that produces descriptive data, data collection methods used are interviews, documentation and literacy regarding Bank Guarantees. The sources of this research are employees of PT. Bank Rakyat Indonesia (Persero) Tbk. Mamba Branch. To find out the function and analyze the Bank Guarantee process as a guarantor for distributors to customers issued by PT. Bank Rakyat Indonesia (Persero) Tbk. Mamba Branch. From the results of this study, Bank guarantee distributor guarantees for customers are included in the type of Bank Guarantee for customers' working capital needs in carrying out business activities. This type of bank guarantee aims to guarantee suppliers (suppliers, factories) who supply raw materials or trade goods used/required by customers in order to fulfill the customer's working capital needs.